Role of Socio-Demographic and Environmental Determinants on Performance of Community Health Workers in Western Kenya - Fletcher Njororai (MDPI AG, 2021)
Background: The performance of community health workers remains an area of significant global focus. The role of community health workers in sub-Saharan Africa has evolved over time in response to changing health priorities, disease burdens, and workforce demands. Recently, Kenya revised its community health strategy in response to challenges faced with the implementation of grassroots primary health care initiative. Implementation of community health programs is often inconsistent, and they vary widely in many attributes. The purpose of this study was to explore factors influencing performance of community health workers in Vihiga County, Western Kenya in light of the political devolution. Methods: The study was a cross-sectional study design that involved a quantitative method of data collection. A sample of 309 participants was selected through cluster and simple random sampling. A self-administered and -structured questionnaire was used to gather data, s, and those who were not able to respond individually were guided by the research assistants. Results: The community health workers were 75.2% females and 24.8% males. Performance was significantly associated with not being employed, (OR = 2.4; 95% CI, 1.4–4.4), secondary education (OR = 0.7; 95% CI, 0.5–1.1), lack of conflict resolution mechanism (OR = 2.2; p = 0.017), lack of support (OR = 1.5; p = 0.03), and community health work not seen as important (OR = 1.5; p = 0.041). Poor communication skills were also more likely to influence performance of community health workers (OR = 0.5; p = 0.050) and poor road network (OR = 0.361; p = 0.000). Conclusions: These findings offer a deeper understanding of the interaction between CHWs contextual situations, structural challenges, and performance. Addressing influential factors of CHWs performance in multi-task settings is important in preventing overtaxing their work capacity and to maintain quality performance as countries move towards universal health coverage. Strategies for incentivizing, attracting, and sustaining men in CHWs is important to broaden perspectives about this critical role in society.